ANALISIS PENAFSIRAN KONSTITUSI HAKIM MAHKAMAH KONSTITUSI DALAM PERUMUSAN PUTUSAN MAHKAMAH KONSTITUSI NO.97/PUU-XIV/2016 TENTANG PENCANTUMAN ALIRAN KEPERCAYAAN DI KARTU TANDA PENDUDUK DAN KARTU KELUARGA - Palendeng, Rivaldo Edward; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This study aims to determine the method of constitutional interpretation used by judges in formulating the decision of the Constitutional Court Number 97 / PUU-XIV / 2016. Interpretation of the constitution means to give the meaning or meaning of a term or collection of terms, in an article or paragraph contained in the Act.This research is prescriptive, when viewed from the objectives of this study it includes normative or doctrinal legal research. Sources of legal materials used in this study are primary legal materials, secondary legal materials and non-legal materials. Data collection techniques used are the study of documents or library materials. The data analysis technique used is deductive.The results showed that the type of constitutional interpretation used by the judge in interpreting the decision of the Constitutional Court Number 97 / PUU-XIV / 2016 related to the inclusion of a flow of trust in the Identity Card and Family Card, namely using the interpretation of originalism, namely textual interpretation.